2006
DOI: 10.1002/cvde.200606495
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Initiated CVD for Polymeric Thin Films

Abstract: A new combinatorial initiated (i)CVD system is fabricated and used to efficiently determine the deposition kinetics for two new polymeric thin films, poly(diethylaminoethylacrylate) (PDEAEA) and poly(dimethylaminomethylstyrene) (PDMAMS). The results of combinatorial depositions are compared to blanket iCVD under identical conditions using the appropriate vinyl monomer with tert-amylperoxide as the initiator. Fourier transform infrared spectroscopy (FTIR) reveals similar chemical structure in blanket and combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The ability to vary properties down the length of a film also allows for combinatorial discovery. For example, multiple filament temperature zones were used to rapidly quantify the kinetics of iCVD poly(diethylaminoethyl acrylate) and poly(dimethylamino methyl styrene) thin film growth 273…”
Section: Characteristics Of Cvd Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability to vary properties down the length of a film also allows for combinatorial discovery. For example, multiple filament temperature zones were used to rapidly quantify the kinetics of iCVD poly(diethylaminoethyl acrylate) and poly(dimethylamino methyl styrene) thin film growth 273…”
Section: Characteristics Of Cvd Polymersmentioning
confidence: 99%
“…Most iCVD takes advantage of the thermal decomposition of the initiator, achieved upon contact with a resistively heated filament array in the vacuum chamber 78, 107, 177, 273, 285, 288. Thermal initiators for iCVD include perfluorooctane sulfonyl fluoride,78 triethylamine, 288 tert ‐butyl peroxide,107 and tert ‐amyl peroxide 285.…”
Section: Unifying Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…In an extended work, another version of the gradient copolymer containing aldehydes and amine gradients was generated, and a subsequent cell-culture study showed that cell-signaling adenovirus was correlated along the copolymer gradients [ 74 ]. A similar combinatorial approach has also been demonstrated to generate poly(diethylaminoethylacrylate) and poly(dimethylaminomethylstyrene) gradients using an initiated CVD system [ 75 ]. The route-controlled click reactions, including a thiol-yne reaction and a copper-free alkyne/azide click reaction, were enabled to create continuous and reverse gradients on a CVD deposited poly[(4-methylpropiolate- p -xylylene)- co -( p -xylylene)] surface.…”
Section: Reviewmentioning
confidence: 99%